2000
DOI: 10.4049/jimmunol.164.11.5675
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Specific Selection of MHC Class II-Restricted Thymocytes in Fetal Thymic Organ Culture

Abstract: Positive and negative selection of thymocytes is determined by the specificity of the TCR and signaling through its associated molecules. We have studied selection of thymocytes bearing a MHC class II-restricted TCR using fetal thymic organ culture. This system allows the addition of peptides to the already diverse panoply of endogenous peptide ligands and is useful for analyzing ligand-specific negative selection of CD4 single positive (CD4SP) thymocytes. The data reveal that the ability of a given ligand to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
3
3
0
Order By: Relevance
“…The CD4 + CD8 + , double positive (DP) compartment was significantly depleted, which was accompanied by a significant increase in CD4 − CD8 + (CD8SP) cells. These observations are consistent with previous data (51, 52). Although the size of the CD4SP compartment remained unchanged, the proportion and number of Foxp3 + cells increased in direct relation to the N72 peptide dose and reached a maximum at a concentration of 1 μM (Figure 4B).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The CD4 + CD8 + , double positive (DP) compartment was significantly depleted, which was accompanied by a significant increase in CD4 − CD8 + (CD8SP) cells. These observations are consistent with previous data (51, 52). Although the size of the CD4SP compartment remained unchanged, the proportion and number of Foxp3 + cells increased in direct relation to the N72 peptide dose and reached a maximum at a concentration of 1 μM (Figure 4B).…”
Section: Resultssupporting
confidence: 94%
“…NTOC with T72 peptide (weak agonist) treatment also induced Foxp3 expression, although it was markedly lower. In contrast, the antagonist I72 peptide, which is sufficient to induce negative selection of T conv cells (Figure 1D, (22, 51)), did not result in the upregulation of Foxp3 (Figure 4C). …”
Section: Resultsmentioning
confidence: 92%
“…Together, these data support the conclusion that even peptides possessing weak affinities for MHC class II molecules can be effective inducers of central tolerance provided that they are displayed in the thymus. These results are consistent with those obtained by Allen and colleagues, who demonstrated that certain antagonistic peptides could negatively select CD4 ϩ T cells (18). In addition, the ability of Ac1-9 to negatively select Ac1-9-specific T cells has been confirmed by Lafaille and colleagues (personal communication).…”
Section: Figsupporting
confidence: 91%
“…3A), whereas more CD4 than CD8 T cells are normally generated in vivo . This tendency has been observed in FTOC (unpublished data and 58–61). When fetal thymi were treated with MCD and cultured in normal FBS, the percentage of CD4 T cells decreased, while that of CD8 T cells increased (Fig.…”
Section: Resultssupporting
confidence: 70%